Sensitivity of Metrics of Phylogenetic Structure to Scale, Source of Data and Species Pool of Hummingbird Assemblages along Elevational Gradients (2012)
ABSTRACT: Patterns of phylogenetic structure of assemblages are increasingly used to gain insight into the ecological and evolutionary processes involved in the assembly of co-occurring species. Metrics of phylogenetic structure can be sensitive to scaling issues and data availability. Here we empirically assess the sensitivity of four metrics of phylogenetic structure of assemblages to changes in (i) the source of data, (ii) the spatial grain at which assemblages are defined, and (iii) the definition of species pools using hummingbird (Trochilidae) assemblages along an elevational gradient in Colombia. We also discuss some of the implications in terms of the potential mechanisms driving these patterns. To explore how source of data influence phylogenetic structure we defined assemblages using three sources of data: field inventories, museum specimens, and range maps. Assemblages were defined at two spatial grains: coarse-grained (elevational bands of 800-m width) and fine-grained (1-km2 plots). We used three different species pools: all species contained in assemblages, all species within half-degree quadrats, and all species either above or below 2000 m elevation. Metrics considering phylogenetic relationships among all species within assemblages showed phylogenetic clustering at high elevations and phylogenetic evenness in the lowlands, whereas those metrics considering only the closest co-occurring relatives showed the opposite trend. This result suggests that using multiple metrics of phylogenetic structure should provide greater insight into the mechanisms shaping assemblage structure. The source and spatial grain of data had important influences on estimates of both richness and phylogenetic structure. Metrics considering the co-occurrence of close relatives were particularly sensitive to changes in the spatial grain. Assemblages based on range maps included more species and showed less phylogenetic structure than assemblages based on museum or field inventories. Coarse-grained assemblages included more distantly related species and thus showed a more even phylogenetic structure than fine-grained assemblages. Our results emphasize the importance of carefully selecting the scale, source of data and metric used in analysis of the phylogenetic structure of assemblages.